Separate Vertical Wirings for the Extra-articular Fractures of the Distal Pole of the Patella - Kim, Young Mo (The Korean Knee Society, 2011)
PURPOSE: To evaluate the usefulness of separate vertical wirings for extra-articular fracture of distal pole of patella. MATERIALS AND METHODS: We have analyzed the clinical results of 18 cases that underwent separate vertical wirings for extra-articular fracture of distal pole of the patella from March 2005 to March 2010, by using the range of motion and Bostman score. Occurrence of complication was also evaluated. Additionally, by taking simple radiographs, the correlation between the postoperative degree of anterior transposition of bone fragment and the time of bone fusion, preoperative length of bone fragment, and occurrence of comminuted fracture were investigated. RESULTS: It took an average of 13.8 weeks for radiological bone union after separate vertical wiring fixation. Flexion contracture was an average of 0.8 degrees and further flexion was an average of 127.6°, and Bostman score was an average of 27.5 points (excellent in 12 cases, and good in 6 cases). On the first postoperative year, average flexion contracture was 0.6 degrees and further flexion was an average of 136.3°, which exhibited increased joint motion and recovery to normal range of motion, and Bostman score was an average of 28.7 points (excellent in 16 cases, and good in 2 cases). There was no statistically significant difference between the preoperative bone fragment length and presence of comminution, and degree of anterior transposition of bone fragment after fracture union on simple radiograph (p=0.175, p=0.146). CONCLUSIONS: We were able to obtain satisfactory clinical results, while preserving the bone fragment by separate vertical wiring fixation for extra-articular fracture of distal pole of patella. Moreover, the method is easy to perform, which is also considered as a useful surgical method for extra-articular fracture of distal pole of patella.